2009
DOI: 10.1021/la903491z
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions Affect Nanoparticle-Mediated Toxicity to Gram-Negative Bacterium Pseudomonas aeruginosa PAO1

Abstract: Nanoscale materials can have cytotoxic effects. Here we present the first combined empirical and theoretical investigation of the influence of electrostatic attraction on nanoparticle cytotoxicity. Modeling electrostatic interactions between cells and 13 nm spheres of zinc oxide nanoparticles provided insight into empirically determined variations of the minimum inhibitory concentrations between four differently charged isogenic strains of Pseudomonas aeruginosa PAO1. We conclude that controlling the electrost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(83 citation statements)
references
References 54 publications
(98 reference statements)
3
80
0
Order By: Relevance
“…It is in this context that the recent reports of the high cytotoxic effects of ZnO nanoparticles (NP) to both prokaryotic and eukaryotic systems pose a grave concern. 4,819 ZnO NP are among the most toxic engineered nanomaterials, especially among oxide NP. 14,20−22 …”
Section: Introductionmentioning
confidence: 99%
“…It is in this context that the recent reports of the high cytotoxic effects of ZnO nanoparticles (NP) to both prokaryotic and eukaryotic systems pose a grave concern. 4,819 ZnO NP are among the most toxic engineered nanomaterials, especially among oxide NP. 14,20−22 …”
Section: Introductionmentioning
confidence: 99%
“…3 The toxicity and antimicrobial effects of ZnO-NPs on microorganisms in activated sludge and on algae and various aquatic species have previously been reported. [8][9][10][11] Industrially released ZnO-NPs could adversely impact the removal of biological pollutants in WWTPs because the microorganisms * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…13 Many studies reported that direct spatial contact between NPs and cell surface is necessary for manifestation of the cytotoxicity, 13,14,16,19 and their interaction is central to the cytotoxicity of NPs. 13,20,21 An apparent mechanism relies on direct damages, either physical (e.g., pitting 22 ) or chemical (e.g., oxidative stress 13 ), of NPs to cell surface (cell wall or cell membrane), which can result in death of the cell. 22 Prolonged contact between the cell and the NPs likely alters the cellular surface properties or integrity 23,24 and triggers the internalization of NPs through endocytosis 25 or direct penetration.…”
Section: ■ Introductionmentioning
confidence: 99%